MobileNetV2 Hyperparameter Optimization for Freshness Classification of Tuna Fish Based on Fish Eye Imagery Using Optuna Tree-structured Parzen Estimator (TPE) - Wa Ode Asriyani; Muhammad Ihsan Sarita; Sutardi Sutardi (RIGGS: Journal of Artificial Intelligence and Digital Business, 2026)
Manually assessing the freshness of tuna (Euthynnus affinis) within traditional auction markets is frequently subjective, inconsistent, and prone to human error. To address these limitations, this study implemented a robust Deep Learning model utilizing the MobileNetV2 architecture to classify fish freshness levels based on ocular imagery into three distinct categories: Fresh, Less Fresh, and Not Fresh. Although the MobileNetV2 architecture is inherently reliable for image classification, conventional manual hyperparameter tuning often leads to suboptimal model configurations and severe overfitting challenges. As a strategic solution, this study implemented the advanced Tree-structured Parzen Estimator (TPE) algorithm through the Optuna framework to automatically optimize critical hyperparameters, including learning rate, dropout rate, optimizer type, and the fine-tune depth of the convolutional layers. Empirical testing results rigorously proved that the strategic integration of Optuna TPE with the MobileNetV2 model successfully provided a significant performance boost. The optimized model achieved an accuracy of 93.51%, representing a substantial increase of 32.04% compared to the 61.47% accuracy observed in the manual baseline model. Correspondingly impressive improvements were recorded in key performance metrics, specifically achieving a Precision of 93.64%, a Recall of 93.37%, and an F1-Score of 93.49%. In conclusion, this research demonstrates that automated hyperparameter optimization using the Optuna TPE framework significantly enhances the reliability, efficiency, and generalization capability of Deep Learning models, establishing a highly accurate and practical solution for the automated detection of tuna freshness in real-world fishery environments.